Pendampingan Kewirausahaan untuk Meningkatkan Kelayakan Bisnis UMKM di Kec. Cempaka, Kota Banjarbaru - Permana, Yudi; Ambarwati, Riris; Firdaus, Firdaus; Fajriyati, Ilisa; Azahraty, Azahraty; Rizky, Siti Raesa (Penerbit Widina, Widina Media Utama, 2025)
MSMEs in general are directed to support efforts to overcome poverty and inequality, create employment opportunities and increase exports, as well as revitalize agriculture and rural areas, which are national development priorities in 2006 (Suyahya, 2017). Within that framework, the development of micro, small and medium enterprises (MSMEs) is directed to provide a significant contribution to the creation of employment opportunities, increasing exports and increasing competitiveness, while the development of micro-scale businesses is directed to contribute to increasing the income of low-income communities, especially the